2014
DOI: 10.1186/1472-6882-14-163
|View full text |Cite
|
Sign up to set email alerts
|

An orally active immune adjuvant prepared from cones of Pinus sylvestris, enhances the proliferative phase of a primary T cell response

Abstract: Background: We have previously demonstrated that an alkaline extract of shredded pinecones yields a polyphenylpropanoid polysaccharide complex (PPC) that functions as an orally active immune adjuvant. Specifically, oral PPC can boost the number of antigen-specific memory CD8 + T cells generated in response to a variety of vaccine types (DNA, protein, and dendritic cell) and bias the response towards one that is predominately a T helper 1 type. Methods: An immune response was initiated by intraperitoneal inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…However, these raw materials were often used in folk medicine in the past, among others in ancient Rome or traditional Chinese and Islamic medicine. Bark, shoots and resins were used as a panacea for, e.g., diseases of the urinary tract, digestive tract, nervous system, respiratory and skin diseases [5][6][7]. Research carried out in recent years has confirmed that compounds present in conifer shoots exhibit therapeutic effects, and shoots are rich sources of polyphenols and have antioxidant properties [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, these raw materials were often used in folk medicine in the past, among others in ancient Rome or traditional Chinese and Islamic medicine. Bark, shoots and resins were used as a panacea for, e.g., diseases of the urinary tract, digestive tract, nervous system, respiratory and skin diseases [5][6][7]. Research carried out in recent years has confirmed that compounds present in conifer shoots exhibit therapeutic effects, and shoots are rich sources of polyphenols and have antioxidant properties [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…by in vivo and in vitro experiments. A more recent study reports on the orally active immune adjuvenant prepared from Pinus sylvestris (L.) cone extracts, which was found to enhance the proliferative phase of a primary T cell response (Bradley et al, 2014). According to the authors certain polyphenylpropanoid polysaccharide complexes are responsible for the measured effects.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 production was high in the Wsamisgt lines ( Fig. 3B,C) because higher amount of acetate group of CM-H 2 DCFDA was cleaved by esterases and its thiol-reactive chloromethyl group reacts with glutathione and other thiols (Bradley et al 2014 (Henzler and Steudle 2000). Accumulated H 2 O 2 in the cell was further reduced by the activity of catalase and ascorbate peroxidase system (Willekens et al 1997, Soshinkova et al 2013.…”
Section: Discussionmentioning
confidence: 98%
“…H 2 O 2 production was high in the Wsamisgt lines (Fig. B,C) because higher amount of acetate group of CM‐H 2 DCFDA was cleaved by esterases and its thiol‐reactive chloromethyl group reacts with glutathione and other thiols (Bradley et al ). H 2 O 2 migrates more easily within the cell and reacts with some cell compounds resulting in lipid peroxides formation which cause high MDA accumulation and membrane damage (Weisany et al ).…”
Section: Discussionmentioning
confidence: 99%